Singapore's educational export strategies: 'branding' and 'selling' education in a favourable global policy marketspace. Issue 1 (2nd January 2023) - Le, Hang; Edwards, D. Brent
ABSTRACT: Since the 1990s, Singapore has firmly established its reputation in the global education policy space as one of the best education systems in the world. However, existing policy transfer literature on Singapore has been mainly interested in Singapore as a decontextualised, ahistorical case, rather than as a unique player in the global education policy sphere. Analysis of how Singapore's educational policies and lessons have been exported to other countries tends to focus on the mediating roles of international assessments and global policy actors like the OECD or McKinsey consultants. What has been much less clear is Singapore's own proactive branding and education export strategies. Guided by the Cultural Political Economy framework, this paper draws attention to how an enabling global education policy context with an insatiable appetite for fast policy lessons has aligned with Singapore's own initiatives to cultivate and export its brand of educational success.